1983
DOI: 10.1136/vr.113.19.441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season, herd size, management system and veterinary practice on the lameness incidence in dairy cattle

Abstract: The incidence of lameness in herds visited by veterinary practitioners in winter (0.87 cases per 100 cows per month) was greater than in summer (0.71 cases per 100 cows per month). The relative proportions of leg lesions and underrun heel were higher, and those of foul-in-the-foot, interdigital hyperplasia and foreign body in the sole were lower in winter than in summer. In winter, leg lesions and aseptic laminitis were most common in cows housed in cowsheds, white line abscess in cows in strawyards and sole u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
1
3

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 0 publications
4
14
1
3
Order By: Relevance
“…Field studies performed showed that the majority of lameness occurs in the rainy season [6][7][8][9][10]12] and that high incidence of lameness usually follows periods of heavy rain [11]. This is in contrast to our findings that have shown a higher proportion of each common lesion occurred in the summer than winter.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Field studies performed showed that the majority of lameness occurs in the rainy season [6][7][8][9][10]12] and that high incidence of lameness usually follows periods of heavy rain [11]. This is in contrast to our findings that have shown a higher proportion of each common lesion occurred in the summer than winter.…”
Section: Discussioncontrasting
confidence: 97%
“…It is interesting that cows housed winter in cowsheds or cubicles with concrete yards remained susceptible to this condition in the summer, whereas cows which were at pasture for most of the year were virtually free of the disease [7]. Murray et al (1996) reported that over 60% of cases of WLD and SU occurred during the winter (November to April) [15]; in contrast, only 24.1% and 12.1% of abattoir reports occurred during this period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subclinical lesions, as sole haemorrhages and varying degrees of heel erosions, and interdigital hyperplasia not associated with lameness were not recorded. The higher distribution of lesions of the rear feet, and of hind lateral claws observed in the present study are findings consistent with earlier surveys (Eddy & Scott, 1980;Russell et al, 1982;Clarkson et al, 1996). The high occurrence of digital and interdigital dermatitis detected in this investigation is probably associated with the poor hygiene conditions observed, but the possibility of the introduction of digital dermatitis into the herds by the purchase of heifers can not be dismissed (Rowlands et al, 1983;Williams et al, 1986;Rodriguez-Lainz et al, 1996;Read & Walker, 1998;Molina et al, 1999).…”
supporting
confidence: 91%
“…The distribution of claw lesions has been approximately 85% higher in the lateral rear claws, where higher loads are supported due to its biomechanic properties (Toussaint Raven, 1985). The principal foot lesions recorded are heel horn erosion (8.7-88%), sole hemorrhage (28-48%), white line diseases (15.6-45%), digital dermatitis (26-29%), sole gap and abscess (10.4-28%), interdigital necrobacillosis (14.3-16.7%), sole ulcer (9-13.6%) and interdigital hyperplasia (1-7%) (Eddy & Scott, 1980;Russell et al, 1982;Clarkson et al, 1996;Bergsten et al, 1998). Recent Brazilian investigation revealed 30.3% of affected lactating dairy cows in the region of Belo Horizonte, being horn erosion (48.5%), interdigital dermatitis (13.5%) and interdigital necrobacillosis (9.6%) the most frequent lesions (Molina et al, 1999).…”
mentioning
confidence: 99%